Monitoring Phospholipase A(2) Activity with Gd-encapsulated Phospholipid Liposomes - Cheng, Zhiliang (Sci Rep, 2014)
To date, numerous analytical methods have been developed to monitor phospholipase A(2) (PLA(2)) activity. However, many of these methods require the use of unnatural PLA(2 )substrates that may alter enzyme kinetics, and probes that cannot be extended to applications in more complex environments. It would be desirable to develop a versatile assay that monitors PLA(2) activity based on interactions with natural phospholipids in complex biological samples. Here, we developed an activatable T1 magnetic resonance (MR) imaging contrast agent to monitor PLA(2) activity. Specifically, the clinically approved gadolinium (Gd)-based MR contrast agent, gadoteridol, was encapsulated within nanometer-sized phospholipid liposomes. The encapsulated Gd exhibited a low T1-weighted signal, due to low membrane permeability. However, when the phospholipids within the liposomal membrane were hydrolyzed by PLA(2), encapsulated Gd was released into bulk solution, resulting in a measureable change in the T1-relaxation time. These activatable MR contrast agents can potentially be used as nanosensors for monitoring of PLA(2) activity in biological samples with minimal sample preparation.